2022
DOI: 10.1590/2179-8087-floram-2021-0095
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Biomass and Diversity of a Late-Successional Subtropical Atlantic Forest in Brazil

Abstract: The highly biodiverse Atlantic Forest has been heavily exploited and its remnant areas, which are mostly composed of secondary forests, cover less than 20% of its original extension. This study analyzed the structure, aboveground biomass (AGB) and species diversity of a secondary evergreen rainforest in the state of Santa Catarina, southern Brazil. Individuals with diameter at breast height ≥ 5 cm on 22 sample plots were measured, totalizing 3.49 hectares of sampled area. A mean AGB of 201.6 Mg ha -1 (standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Fabaceae is considered the most common family in tropical Amazonian forests [31] and the third largest family of angiosperms [101]. Due to symbiotic nitrogen fixation in Fabaceae species [102], they can drive early ecological succession [21,61] and they are important in secondary forest and successful restoration practices [103].…”
Section: Tree Species Dominance and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabaceae is considered the most common family in tropical Amazonian forests [31] and the third largest family of angiosperms [101]. Due to symbiotic nitrogen fixation in Fabaceae species [102], they can drive early ecological succession [21,61] and they are important in secondary forest and successful restoration practices [103].…”
Section: Tree Species Dominance and Compositionmentioning
confidence: 99%
“…Recent studies in the Amazon have reported the ecological mechanisms of human activity influence on the recovery of species diversity, species composition, and AGB [24][25][26][27]. Many studies have shown that the stand forest age [28,29], species number [30], species diversity [31], species composition [32], and forest height [33] are positively correlated with AGB levels in secondary forests. In addition, a recent study showed that forest structure (e.g., forest height) conditions the effects of species richness on AGB accumulation [24].…”
Section: Introductionmentioning
confidence: 99%